Effects of Mineral Activators on Hydration Properties of Ternary, Low-Heat Blended Cement with Abundant Ground Granulated Blast-Furnace Slag - Woo Choi, Sung; Yong Kim, Gyu; Hyun Ryu, Deuk; Woo Back, Chul (Asian Journal of Chemistry, 2015)
Hydration properties and use of blended cements with various types of mineral activators were evaluated for the purpose of developing an environment-friendly, low-heat blended cement using a high proportion of ground granulated blast-furnace slag and fly ash, thus reducing the proportion of Portland cement mix by up to 10 %. The results showed that a mixture of plaster and quicklime as a mineral activator, at 5 % of total binder content, can maintain performance comparable with standard, commercial low-heat cements and importantly, results in a significant reduction in concrete's hydration heat.